The return of the walls in the global era - Zuin, João Carlos Soares; Silva, Laís Barreto da (Laboratório Editorial Faculdade de Ciências e Letras, 2016)
This article describes and analyzes some of the factors that influence the construction of the walls in the global age. The first part we analyzed the sense of construction of emergency and fear policy in Europa. The second part we discusses the political construction of State racism and the discriminatory actions against poor immigrants and refugees. In the third part we analyze the aesthetics of the walls produced in the global era and their economic, political and cultural functions in contemporary capitalist society.